Implementation Of History Learning In The Independent Learning Curriculum In High Schools - Roni Irawan (Yayasan Insan Mulia Bima, 2024)
This research aims to reveal the implementation of history learning in the independent learning curriculum by looking at the planning of history learning in the independent curriculum, the implementation of history learning in the independent learning curriculum and evaluating the implementation of history learning in the independent learning curriculum. This research uses a qualitative research method with a qualitative descriptive approach, data collection techniques using observation, interviews and documentation, data analysis techniques used using data triangulation, source triangulation, researcher triangulation, method triangulation and theory triangulation while for data validity using data analysis techniques. Based on the research results, it shows that (1) planning history learning in the independent curriculum, schools prepare an operational curriculum which is the basis for understanding learning planning, teachers prepare learning plans, (2). The implementation of history learning in the independent curriculum is different from the 2013 curriculum, history learning uses scientific learning using the discussion method while the independent curriculum uses the differentiation method using a project to strengthen the profile of Pancasila. (3). Evaluation of history learning, students are very active and there are no obstacles except that the learning hours are tight and the history subject in the Ganji semester applies